2011
DOI: 10.1111/j.2044-8287.2011.02025.x
|View full text |Cite
|
Sign up to set email alerts
|

An examination of hardiness throughout the sport injury process

Abstract: Objectives. This primary objective of the study was to examine the direct and moderating effects of hardiness on the prediction of sport injury, and the direct and indirect effects of hardiness on athletes’ responses to injury.Design. This study employed a longitudinal methodological design. Specifically, the injury status of 694 asymptomatic participants was monitored for 2 years. From the original sample, 104 athletes subsequently became injured and then completed a number of questionnaires throughout their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 166 publications
(463 reference statements)
3
37
0
6
Order By: Relevance
“…Research suggests that junior athletes may be particularly at risk (e.g., Frisch, Croisier, Urhausen, Seil, & Theisen, 2009;Renshaw & Goodwin, 2016). Importantly, there is increasing evidence highlighting the importance of psychological factors in contributing to the risk of injury in junior athletes (e.g., Ivarsson, Johnson, Andersen, Fallby, & Altemyr, 2015;Steffen, Pensgaard, & Bahr, 2009;Wadey, Evans, Hanton, & Neil, 2012).…”
Section: Perfectionism and Injurymentioning
confidence: 99%
“…Research suggests that junior athletes may be particularly at risk (e.g., Frisch, Croisier, Urhausen, Seil, & Theisen, 2009;Renshaw & Goodwin, 2016). Importantly, there is increasing evidence highlighting the importance of psychological factors in contributing to the risk of injury in junior athletes (e.g., Ivarsson, Johnson, Andersen, Fallby, & Altemyr, 2015;Steffen, Pensgaard, & Bahr, 2009;Wadey, Evans, Hanton, & Neil, 2012).…”
Section: Perfectionism and Injurymentioning
confidence: 99%
“…Consistent with Williams and Andersen's (42) model and associated research (25,32), findings revealed that as major life events (i.e., total and negative) and the number of previous injuries increased, the likelihood of injury also increased. Wadey et al (39) recently suggested that one possible explanation for the effect of major life events on injury occurrence is that these events ofien require a substantial amount of physiological, psychological, and behavioral readjustment, which, in line with Williams and Andersen's model, may have the potential to exacerbate the stress response and as a result the likelihood of injury. In terms of the effect of previous injuries, Williams two explanations as to why this preinjury variable increases the likelihood of injury.…”
Section: Discussionmentioning
confidence: 86%
“…The number of injuries sustained by the participants served as the outcome variable for the prediction of injury occurrence (39). An injury was defined as a medical problem resulting from sport participation that prevented normal training and competition for a minimum period of 2 wk.…”
Section: Previous Injuries Williams and Andersenmentioning
confidence: 99%
See 2 more Smart Citations